Pengaruh Viskositas Minyak Rem dan Tekanan Fluida Terhadap Jarak Pengereman Pada Sepeda Motor 125 CC - Arrediaz Bhakti Inusantara; Purwoko Purwoko (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The braking system is a crucial component that affects driving safety on motor vehicles, especially motorcycles. The purpose of this study was to determine how brake fluid viscosity and brake fluid pressure affect braking distance. Brake fluids A (12,001 cSt), B (11,120 cSt), and C (10,958 cSt) are three types of brake fluids that vary, along with brake fluid pressure, which ranges from 1.5 to 4.5 bar. A 7 mm bolt that is 70 mm long and drilled into the brake lever is used to limit the pressure. Based on the results of the study, braking distance is affected by fluid pressure and viscosity. With the same fluid pressure of 4.5 bar, brake fluid A is able to brake at the farthest distance of 25.01 meters, brake fluid B is able to brake at the middle distance of 23.12 meters, and brake fluid C is able to brake at the shortest distance of 21.79 meters.